2023
DOI: 10.55236/tuara.1134986
|View full text |Cite
|
Sign up to set email alerts
|

The student's evaluation of the delivery of the theoretical courses due to warning mask and social distance during the pandemic condition

Abstract: The pandemic condition changed the style of teaching and learning in the wide world. Particularly some measurements such as warning masks and social distance influenced the quality of the education in the higher education. A five-scale Likert questionnaire was designed to ask the architecture students to evaluate the quality of the delivery of the theoretical courses in the department. SPSS was applied to analyze data with quantitative methods. The results revealed that the students generally were satisfied wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Despite both negative and positive literature on the influences of COVID-19 on education, the results of the research demonstrated that the students preferred to follow their style of activities in the design studio (Tafahomi, 2022a;Tafahomi, 2022b) as mentioned in terms of interaction through desk-crits by Schon (Schon, 1987). The studies mentioned the positive effects of the pandemic time on blended learning (Delialioglu & Yildirim, 2007;Gulbahar & Madran, 2009), however, the students' answers demonstrated that they preferred a physical class for social interaction.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Despite both negative and positive literature on the influences of COVID-19 on education, the results of the research demonstrated that the students preferred to follow their style of activities in the design studio (Tafahomi, 2022a;Tafahomi, 2022b) as mentioned in terms of interaction through desk-crits by Schon (Schon, 1987). The studies mentioned the positive effects of the pandemic time on blended learning (Delialioglu & Yildirim, 2007;Gulbahar & Madran, 2009), however, the students' answers demonstrated that they preferred a physical class for social interaction.…”
Section: Discussionmentioning
confidence: 95%
“…Particularly, the physical classes were recommended to use alternative scenarios such as local parks, open spaces, tennis courts, or football pitches. However, the activities in the design studios included a long list of activities that students normally preferred to stay in the design due to practical activities (Tafahomi, 2021a) and even theoretical courses (Tafahomi, 2022b). However, the study exposed positive effects of the COVID-19 on the education of architecture program even in the first year (Abu Alatta et al, 2023;Tafahomi, 2021c).…”
Section: Introductionmentioning
confidence: 98%